EFFECTS OF MONOCHROMATIC LIGHT ON PERFORMANCE, EGG QUALITY, YOLK CHOLESTEROL AND BLOOD BIOCHEMICAL PROFILE OF LAYING HENS - F. Yenilmez1; S. N. Saber; U. Serbester; L. Celik (Journal of Animal and Plant Sciences, 2020)
The present study was conducted to investigate whether monochromatic light affects the production performance, egg quality and some plasma parameters of layers. In this study, white and green fluorescent lamps were used to illuminate Brown-Nick hens for 8 weeks. Light sources made uniform to a light intensity of 15 lx. Forty-seven-week-old layers were divided into 2 groups of similar mean weight comprising 16 birds each and housed in individual cages. A 16:8 hours light:dark photoperiod was employed. The layers were exposed to conventional ambient temperature and 50-60% relative humidity for 24h per day. Performance was evaluated by recording feed intake, egg weight and egg production on daily basis; egg quality and egg cholesterol level on weekly basis; and blood parameters on 56th day of the experiment. The results indicated that green light application did not have any significant effect on feed intake, feed conversion ratio, egg production, total number of eggs, total egg weight, average egg weight, cholesterol level of egg yolk and egg quality of laying hens. However, green light application affected egg yolk color a* and b* values, but decreased serum albumin concentration. The results suggest that green light application may improve the yolk color of laying hens.
Keywords: Light color; egg cholesterol; egg quality; Brown-Nick hen; serum parameters